(untitled) (Texas Journal of Medical Science, 2022)
Gout is the most common type of inflammatory arthritis that is caused by the deposition of monosodium uric acid crystals in and around peripheral joints. This study was carried out to investigate biochemical and genetic aspects of gout arthritis. Two approaches were adopted, the first included the study of some biochemical parameters (serum uric acid, creatinine and WBC count) in gout patients and the second comprised the study of the role of gene in the variation site (rs2231142) in the incidence of gout. Blood samples were collected from 25 gout patients and 25 healthy subjects as control group, during the period from December 2020 to May 2021, at the Rheumatology Department of Clinic Consultant at AlYarmouk Hospital. Personal information for each patient was obtained. Uric acid and creatinine were measured to study relationship between kidney function and the disease. White blood cells were counted to investigate the inflammation status. The results revealed that Both serum uric acid and serum creatinine concentration were significantly higher in gout patients as compared to controls. There is a positive correlation between gout and WBC count because of inflammation